TINGKAT PERTUMBUHAN ASPERGILLUS FLAVUS SP DAN PEMBENTUKAN AFLATOKSIN PADA BERBAGAI METODE PENYIMPANAN DENGAN KADAR AIR BIJI JAGUNG PAKAN - Hapsari Okgianti Yusuf (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
The objectives of this study are 1) To determine the best storage method for maize forgrowth Aspergillus Flavus sp and aflatoxin formation, 2) To determine the best water content regulation during storage of maize which can suppressgrowth Aspergillus Flavus sp and aflatoxin formation. This research consisted of two stages, namely corn sampling and main research. In the main research, analysis of moisture content with different storage methods, growth analysis of Aspergillus Flavus sp and levels of aflatoxin using the ELISA method was carried out. The statistical analysis method used was a completely randomized design with two factors. From the results of the Water Content analysis, the highest increase in water content for all treatments was seen in the storage treatment using HDPE plastic at 30% moisture content, namely the initial water content of 30 increased to 35.55%, with an increase of 5.55%. Whereas the lowest increase in water content for all treatments was seen in the storage treatment with spread at 15% moisture content, namely with an initial water content of 15% to 15.64% with an increase of 0.64%. Theincrease in the growth of Aspergillus flavus sp highestfor all treatments was seen in the storage treatment by packaging using HDPE plastic at 30% moisture content, namely thegrowth rate Aspergillus flavus sp initialof 1.97 x 103 increased to 88.93 x103, while the increase in the growth of Aspergillus flavus sp. The lowest for all treatments was seen in the storage treatment with spread at 15% moisture content, namely the growth of Aspergillus flavus sp early 1.54 x 103 to 33.34x103. The highest aflatoxin test was at the water content level of 30% with the storage method packed using HDPE plastic, while the lowest aflatoxin test result was at the 15% moisture level with the storage method spread out